2021
DOI: 10.14336/ad.2020.1226
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-butylphthalide Increases Collateriogenesis and Functional Recovery after Focal Ischemic Stroke in Mice

Abstract: Recent evidence indicates that collateral circulation is critical for the outcome of ischemic stroke. DL-3-n-butylphthalide (NBP), a synthesized compound based on an extract from seeds of celery Apium graveolens Linn , has been used as a therapeutic drug, showing multiple neuroprotective and regenerative activities. A potential effect of NBP on collateral arterial regulation is unknown. We examined the effects of NBP on arteriogenesis of collateral arteries in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…The results showed that the medium-dose DL-NBP alleviated MCAO-induced neurologic deficits, brain water content, and infarction area and improved nerve function and ischemic brain injury compared to the MCAO group. Previous research not only reached the same conclusion Wei et al, 2021) but also proved that BBB destruction could increase tissue swelling and lead to brain damage (Song et al, 2022). These three studies confirm the successful establishment of a model of hypoxic-ischemic brain injury but also serve as a reminder of the damage to the BBB in this injury, which has also been mentioned in other articles (Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results showed that the medium-dose DL-NBP alleviated MCAO-induced neurologic deficits, brain water content, and infarction area and improved nerve function and ischemic brain injury compared to the MCAO group. Previous research not only reached the same conclusion Wei et al, 2021) but also proved that BBB destruction could increase tissue swelling and lead to brain damage (Song et al, 2022). These three studies confirm the successful establishment of a model of hypoxic-ischemic brain injury but also serve as a reminder of the damage to the BBB in this injury, which has also been mentioned in other articles (Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…The primary clinical treatment for ischemic stroke involves thrombolytic drugs, antiplatelet aggregation drugs, and anticoagulants. However, thrombolytic therapy must be carried out within a limited treatment window, dramatically limiting its clinical application (Derek Barthels, 2020;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Drug concentrations were chosen based on previous reports. Some previous studies give us a clue on employing the experimental concentration of NBP ( 43 , 47 ). Combined with our pilot study, 50 mg/kg (low) and 100 mg/kg (high), the two comprehensive considerations were applied in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…NBP downregulates AQP4 and matrix metalloprotease-9 (Mamtilahun et al, 2021), which may help explain how it protects the blood-brain barrier in the acute phase of ischemic stroke (Hu et al, 2014;Feng et al, 2018;Li et al, 2019b). NBP can promote collateriogenesis, neurogenesis, and angiogenesis; increase axonal growth; and strengthen white matter integrity (Yang et al, 2015;Sun et al, 2017;Zhou et al, 2019;Wang et al, 2020c;Liu et al, 2021b;Qu et al, 2021;Wei et al, 2021). NBP can accelerate the recovery of cerebral blood flow and reduce cognitive impairment (Xiong et al, 2017;Li et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%